E-business motives in transformation of SMEs to E-SMEs - Güngör, Pınar (My University, 2003)
Proliferation of the Internet and the latest developments in information and communication technologies are creating a global and competitive platform for businesses to conduct commercial transactions. This fact has critical implications especially for small and medium sized enterprises because they are considered to be the backbone of all economies. It has been estimated that 99 per cent of the enterprises operating in Turkey are SMEs. They create 79.7 per cent of the employment and 38 per cent of the value added. SMEs are generally considered to be flexible, adaptive and innovative organizations, and these characteristics make them a good fit for electronic commerce. However, they are being left behind in the developing digital world. They need to be informed about the opportunities offered by e-business and be supported in order to adopt e-business. This study focused on the transformation of SMEs in Turkey to e-SMEs. Transformation stages of SMEs to e-SMEs were discussed which included web presence, motives for involvement with e-business initiatives, support needed by SMEs during or before the implementation of e-business initiatives, major inhibiting factors influencing decisions not to take-up e-business and difficulties involved with e-business implementation. A research is conducted for investigating the SMEs' perceptions of e-business opportunities and threats and type of support needed. The findings of the research indicate that Turkish SMEs are in the web presence stage of their transformation to e-SMEs, and competitive forces are the major motives for them to implement e-business.

İnternetin yaygınlaşması ve bilişim ve iletişim teknolojilerinde son yıllarda yaşanan gelişmeler, işletmelerin ticari işlerini yürütebilmesi için küresel ve rekabetçi bir platform yaratmaktadır. Bu gerçek, özellikle küçük ve orta ölçekli işletmeler (KOBİ) için kritik önem taşımaktadır, çünkü bu işletmelerin tüm ülkelerde ekonomilerin belkemiğini oluşturduğu kabul edilmiştir. Türkiye'deki teşebbüslerin % 99'unu KOBİ'lerin oluşturduğu bilinmektedir. Bunlar Türkiye'deki işgücünün % 79.7'sini ve katma değerin % 38'ini oluşturmaktadır. KOBİ'lerin genellikle esnek yapıları, ilerici ve yeniliğe açık kuruluşlar olmaları nedeniyle elektronik ticarete çok iyi uyum sağlayabilecekleri düşünülmektedir. Ancak, KOBİ'ler gelişen dijital dünyanın gerisinde bırakılmaktadırlar. Bu kuruluşların elektronik işe uyum sağlayabilmeleri için elektronik iş ve ticaretin sunduğu fırsatlar konusunda bilgilendirilmeleri ve bu konularda desteklenmeleri gerekmektedir. Bu çalışma, Türkiye'deki KOBİ'lerin elektronik işletmelere dönüşüm aşamalarını konu almaktadır. Bu konu dahilinde, KOBİ'lerin internet ağlarında varolması, onları elektronik işletme olmaya yönlendiren sebepler, elektronik işletmeye dönüşümleri sırasında ihtiyaç duydukları destekler, elektronik işletmeye geçmeyen KOBİ'lerin ise hangi nedenlerden dolayı bu kararı verdikleri ve elektronik ticareti uygulayanların ise bu süreçte karşılaştıkları zorluklar anlatılmaktadır. KOBİ'lerin elektronik işin sunduğu fırsat ve tehditleri nasıl algıladıklarını ve ne tür desteğe ihtiyaçları olduklarını araştırmak amacıyla bir anket düzenlenmiştir. Bu anketin sonucunda ise, KOBİ'lerin henüz internette web sayfası kurma aşamasında oldukları ve onları elektronik işletmeye yönlendiren en önemli sebebin rekabet avantajı yakalamak olduğu görülmüştür.
Keywords: İşletme